Effect of Tin on Hot Ductility and High-temperature Oxidation Behavior of 20CrMnTi Steel - Peng Hong-bing; Chen Wei-qing; Chen Lie; Guo Dong (High Temperature Materials and Processes, 2014)
The hot ductility and high-temperature oxidation behavior of 20CrMnTi steel with 0.02% Cu and x% Sn (0.004 ⩽ x ⩽ 0.049) were investigated. The results show that tin has no significant effect on tensile strength of sample with less than 0.049% Sn. The critical temperature where the hot ductility reduces dramatically rises with the increase of tin content while the hot ductility decreases with its increase. The average tin content at austenite grain boundaries (GB) and substrate is 0.108% and 0.045% respectively in the specimen containing 0.049% tin quenched after heated to 1223 K and held for 600 s. Sn-segregation at the GB deteriorates the hot ductility. There is no direct relationship between the cause of the ductility trough and tin. However, Sn-segregation at the GB causes it to deepen a lot. The tin content should be controlled below 0.021%, which would not deteriorate the hot ductility significantly. There is no tin-enrichment at the scale/substrate interface when tin content is less than 0.049%. Moreover, although Sn is enriched under the steel surface, any liquid Sn-enrichment wasn't observed at the oxide/steel interface even in as high as 0.45% Sn-bearing steel with 0.02% Cu.